Trade Wars and Trade Talks - Grossman, Gene M.; Helpman, Elhanan (Journal of Political Economy, 1995)
When governments meet in the international arena, their actions reflect the political situations at home. Previous studies of trade relations have focused on governments that are immune from political pressures and that act as benevolent servants of the public interest. Here we introduce domestic politics into the analysis of international economic relations. We study the interactions between national leaders who are concerned with both providing a high standard of living to the general electorate and collecting campaign contributions from special-interest groups. Our analysis sheds light on the determinants of the structure of protection in noncooperative and cooperative policy equilibria.